Building a resilient infrastructure: challenges of rural transportation in Soba Local Government Area, Kaduna State, Nigeria - Abdulkadir Yahaya Muhammed; Hajara Salahudeen; Dauda Zubairu (Goodwood Publishing, 2021)
Purpose: Despite the economic importance of rural transportation, it is often being neglected. This study is aimed at identifying the challenges of rural transportation in the Soba Local Government Area to recommend measures for tackling them. Research methodology: Both interview and observation methods were applied in data collection and purposive sampling was adopted in choosing rural areas covered by the study. However, 140 interviewees were asked from five areas chosen. The interviewees were transporters, commuters and other stakeholders in rural transportation. Descriptive and inferential techniques were used in data analysis. Results: The results revealed that road conditions were in a deplorable state, about 39% of interviewees considered them bad and only 25% said they were good. About 43% of the interviewees said transport fare was expensive. About 41% of vehicles used were in bad shape, 84% of the interviewees said passengers often spend more than 30 minutes to get a vehicle. The result also showed that there was a significant relationship between good transportation network and economic development. Limitations: The scope of the study should have been wider to cover the whole eleven political wards of the local government area. The sampling method used might not necessarily give a true reflection of what happens. Contribution: Rural transport contributes immensely to the development of the world. It creates jobs, access to markets and infrastructure. This study is consistent with Sustainable Development Goals (SDGs) goal 9 and 11. Which are aimed at building resilient infrastructure and settlements. Keywords: Local, Government, Area, Rural, Transportation